Modeling the relationship between grading, moisture content and screen apertures in groundnut decortication - Aminu, S.; Akande, F. B.; Ola, F. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2018)
Whole Groundnut kernels free of bruises attract foreign exchange earnings. The appropriate selection and the interactions between the processing parameters in groundnut decortication produces clean kernels. Therefore, the focus of this study was to establish mathematical equations in order to explore and predict the possible relationships between the process inputs (grading, moisture content and screen apertures) and the measured output (clean kernels, bruised kernels and split kernels) in decorticating three selected varieties of groundnut in-shell commonly cultivated in Nigeria with a view of maximizing their kernel quality. The varieties were Samnuts 10, 14 and 18. In doing this, individual relationships were explored one at a time by keeping other process parameters constant to ensure clear interpretations. The relationships between grading, moisture content and screen apertures versus the response (efficiency of clean, bruised and split kernels) were approximated using a linear and nonlinear (quadratic or polynomials) functions. Regression analysis and design expert software (multivariate) were used to develop the mathematical models that describe the relationships between these inputs and the measured outputs.